Understanding the properties of bronze-bonded diamond grinding wheels on process behaviour. Issue 1 (2022) - Bergmann, Benjamin; Dzierzawa, Patrick
Abstract: The process behaviour of bronze-bonded diamond grinding wheels depends on the selected bond composition and the sintering parameters. Understanding these dependencies is the key to a knowledge-based manufacturing process for grinding wheels. In this study, the wear behaviour of different bond compositions and sintering parameters is investigated. It could be shown that the predominant wear mechanism is mainly grain flattening and that it depends on the critical bond strength. Finally, these findings were used to analyse the workpiece quality in dependence of the variously manufactured grinding wheels. This enables a new approach for the production of load adapted grinding wheels.